Post-pandemic planning: Do we have enough and efficient access to parks? - Alkhaja, Nour; Alawadi, Khaled; Ibrahim, Hasan Manan (Frontiers in Built Environment, 2023)
The COVID-19 pandemic has placed neighborhood parks as a key asset in mitigating the negative implications of extended lockdowns, when parks turned into a sanctuary for residents. With increased scholarly work focusing on developing pots-pandemic neighborhoods, providing access to community parks via efficient routes, is central to such debate. Network connectivity provides a comprehensive assessment of the efficiency of network systems. A total of 16 samples, from the city of Abu-Dhabi, have been selected to study their network connectivity, with regard to accessing parks. Three distance-based connectivity measures are used: the pedestrian route directness (PRD), the count of redundant routes (RC), and the route redundancy index (RI). The samples reflect different street’s typologies and their urban form attributes are quantified. Connectivity analyses results are interrupted with regard to the quantified physical attributes. Findings indicate that gridded, and semi-gridded layouts provide more direct routes to parks, but less route’s redundancy. Conversely, interlocked, and fragmented networks, when having sufficient intersection densities, have less direct routes but more redundancy. The inclusion of alleyways proved to alter typologies into gridded ones and improve both route directness and redundancy. The majority of the selected samples reported sufficient levels of route directness. The current design and planning guidelines, implemented by the Department of Transport and Municipalities are overly descriptive with regard to how neighborhood parks are accessed; therefore, the study’s methodology provides a possible more evidence-based approach to policy development.